Comparative analysis between dermoid and epidermoid cyst - Piedad Elizabeth Acurio Padilla; Alejandra Micaela Rodríguez Acurio; José Fernando Trávez Valencia (Universidad Médica Pinareña, 2023)
Introduction: epidermoid and dermoid cysts are benign lesions that often simulate a brain tumor, both clinically and imaging-wise.